Multiplex profiling of inflammation-related bioactive lipid mediators in Toxocara canis- and Toxocara cati-induced neurotoxocarosis. - Patrick Waindok; Elisabeth Janecek-Erfurth; Dimitri Lindenwald; Esther Wilk; Klaus Schughart; Robert Geffers; Laurence Balas; Thierry Durand; Katharina Maria Rund; Nils Helge Schebb; Christina Strube (Public Library of Science (PLoS), 2019)
BACKGROUND:Somatic migration of Toxocara canis- and T. cati-larvae in humans may cause neurotoxocarosis (NT) when larvae accumulate and persist in the central nervous system (CNS). Host- or parasite-induced immunoregulatory processes contribute to the pathogenesis; however, detailed data on involvement of bioactive lipid mediators, e.g. oxylipins or eico-/docosanoids, which are involved in the complex molecular signalling network during infection and inflammation, are lacking. METHODOLOGY/PRINCIPAL FINDINGS:To elucidate if T. canis- and T. cati-induced NT affects the homeostasis of oxylipins during the course of infection, a comprehensive lipidomic profiling in brains (cerebra and cerebella) of experimentally infected C57BL/6J mice was conducted at six different time points post infection (pi) by liquid-chromatography coupled to electrospray tandem mass spectrometry (LC-ESI-MS/MS). Only minor changes were detected regarding pro-inflammatory prostaglandins (cyclooxygenase pathway). In contrast, a significant increase of metabolites resulting from lipoxygenase pathways was observed for both infection groups and brain regions, implicating a predominantly anti-inflammatory driven immune response. This observation was supported by a significantly increased 13-hydroxyoctadecadienoic acid (HODE)/9-HODE ratio during the subacute phase of infection, indicating an anti-inflammatory response to neuroinfection. Except for the specialised pro-resolving mediator (SPM) neuroprotectin D1 (NPD1), which was detected in mice infected with both pathogens during the subacute phase of infection, no other SPMs were detected. CONCLUSIONS/SIGNIFICANCE:The obtained results demonstrate the influence of Toxocara spp. on oxylipins as part of the immune response of the paratenic hosts. Furthermore, this study shows differences in the alteration of the oxylipin composition between T. canis- and T. cati-brain infection. Results contribute to a further understanding of the largely unknown pathogenesis and mechanisms of host-parasite interactions during NT.